2017
DOI: 10.3748/wjg.v23.i16.2912
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivoantioxidative and hepatoprotective activity of aqueous extract of Cortex Dictamni

Abstract: AIMTo investigate the antioxidant and hepatoprotective effects of Cortex Dictamni aqueous extract (CDAE) in carbon tetrachloride (CCl4)-induced liver damage in rats.METHODSThe in vitro antioxidant effect of CDAE was investigated using α,α-diphenyl-β-picrylhydrazyl (DPPH), 2,2’-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS), β-carotene bleaching, reducing power, and thiobarbituric acid reactive substance assays. A linoleic acid system, including ferric thiocyanate (FTC) and thiobarbituric acid (TBA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Taken together, the results of the in vitro and in vivo antioxidant evaluation indicated that T. tetraptera showed good antioxidant activity, which may be attributable to its direct function in scavenging free radicals [32, 33]. The hepatoprotective properties of a diversity of plants have been previously reported, and these protective properties have been correlated with a high antioxidant potential [30]. Damage to the liver can be assessed through the determination the activity of enzymes such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the results of the in vitro and in vivo antioxidant evaluation indicated that T. tetraptera showed good antioxidant activity, which may be attributable to its direct function in scavenging free radicals [32, 33]. The hepatoprotective properties of a diversity of plants have been previously reported, and these protective properties have been correlated with a high antioxidant potential [30]. Damage to the liver can be assessed through the determination the activity of enzymes such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, co-transfection with pre-miR-144 significantly suppressed luciferase activity of the reporter containing the wild-type 3′-UTR of the Nrf2 mRNA ( Figure 4C ), indicating that miR-144-3p down-regulated Nrf2 expression via directly binding to the putative binding site of Nrf2 mRNA. In this line of thinking, we tested the effect of lico A on Nuclear factor E2-related factor (Nrf2) expression, and the western blot results revealed lico A also decreased Nrf2 and its down-stream γ-glutamylcysteine synthetase catalytic subunit (γ-GCSc) protein levels ( Li et al, 2017 ) in H292 cell line ( Figure 4D ). To prove if lico A decreased Nrf2 expression via increasing miR-144-3p, first, co-transfection experiment of pre-miR-144 and lico A was conducted, and the results substantiated that lico A could enhance the decrease of Nrf2 protein level caused by miR-144-3p ( Figure 4E ).…”
Section: Resultsmentioning
confidence: 99%
“…I/R injury induces mitochondria to produce high level of ROS, including superoxide anion (O 2 -•), hydroxyl radical (OH -•) and hydrogen peroxide H 2 O 2 (39). Excessive amounts of ROS cause damage to mitochondria, inducing mPTP opening and mitochondrial depolarization (40). Furthermore, an increased concentration of cytosolic Ca 2+ activates a variety of cell death-associated processes following I/R.…”
Section: Discussionmentioning
confidence: 99%